Teacher Renumeration and Job Satisfaction in Private Secondary Schools: A Case Study in Kakoba, Mbarara City South Division - Kanshabe, Scovia; Twebaze, Richard; Barigye, Enock (East African Journal of Education Studies, 2024)
The study examined the correlation between remuneration and job satisfaction among teachers in private secondary schools in Kakoba, Mbarara City South Division. The research objectives were to evaluate the levels of teachers' remuneration, assess their job satisfaction, and establish the relationship between remuneration and job satisfaction in the specified schools. A quantitative research design was employed to ensure the accuracy and relevance of the data collected. The study focused on teachers in private secondary schools in Kakoba, Mbarara City South Division, with a sample size of 40 teachers selected from a total of 57 respondents. Teachers were chosen using a stratified random sampling method from each school, with the selection of private schools based on purposive sampling. Data collection was facilitated through an online questionnaire created using Google Forms. Remuneration was analyzed in terms of basic pay, while teachers' job satisfaction was evaluated based on their overall contentment with the work environment concerning their remuneration. Monthly salaries ranged from 200,000 shillings to 1,000,000 shillings, and job satisfaction levels were rated on a scale of 1-5, with teachers earning higher salaries reporting lower levels of job satisfaction. Inferential analysis, specifically the Pearson correlation coefficient, revealed a very low positive correlation (0.117) between remuneration and job satisfaction levels, indicating that factors beyond remuneration significantly influence teachers' job satisfaction. The study highlighted that 68.3% of the participants expressed dissatisfaction with their monthly salaries, while only 31.7% felt adequately satisfied. The study concluded that there is no statistically significant relationship between teachers' remuneration and their job performance. As a recommendation, it suggested an increase in the remuneration of private school teachers in Kakoba, Mbarara City South Division based on the findings to potentially enhance job satisfaction levels among teachers